THE EFFECT OF WORK STRESS AND WORK FAMILY CONFLICT ON TURNOVER INTENTION WITH JOB SATISFACTION AS AN INTERVENING VARIABLE - Prilia Diah Nita (CV. Era Digital Nusantara, 2022)
This study aims to examine the effect of Work Stress and Work Family Conflict on Turnover Intention with Job Satisfaction as an intervening variable. The population in this study were employees. The sample selection technique in this study is a saturated sample technique that uses the entire population of 40 employees. The method used in this study is a quantitative method with primers analyzed by Path Analysis with the help of the SPSS Statistic 22 program. The results obtained in this study indicate that there are 5 accepted hypotheses: (1) Work Stress has a significant effect on Turnover Intention, (3 ) Work Stress has a significant negative effect on Job Satisfaction, (5) Job Satisfaction has a negative effect on Turnover Intention, (6) Job Satisfaction can mediate the effect of Work Stress on Turnover Intention of BRISyariah KC Palembang employees, (7) Job Satisfaction can mediate the effect of Work Family Conflict on the Turnover Intention of employees and 2 rejected hypotheses: (2) Work Family Conflict has no significant effect on Turnover Intention, (4) Work Family Conflict has no significant effect on Job Satisfaction.